Relationships Matter: Assessing the Impacts of a Marine Protected Area on Human Wellbeing and Relational Values in Southern Tanzania - Baker, Dana; Murray, Grant; Kaijage, Jackson; Levine, Arielle; Gill, David; Makupa, Enock (Frontiers in Marine Science, 2021)
The push to meet global marine conservation targets has significantly increased the scope and scale of marine protected areas (MPAs) worldwide. While the benefits derived from MPA establishment are often optimistically framed as a “win-win” for both marine biodiversity and for the wellbeing of coastal peoples, this assumption is challenged for several reasons, including the fact that current science and practice frequently fails to account for the full impact of MPAs on human wellbeing. This context poses a danger that the context specific, place based aspects of wellbeing, like relations to others and the marine environment, will not be accounted for, examined, or reported in evaluation and decision-making processes. To address this challenge, this research investigates how MPA implementation can change and challenge the relational wellbeing and relational values of small-scale fishers (SSFs) living in Mnazi Bay-Ruvuma Estuary Marine Park, Tanzania. Fieldwork occurred over 2019-2020 and used qualitative data collection methods, including: 140 semi-structured interviews, document analysis, and observation. Results highlight a dynamic interaction between the MPA and SSFs relational wellbeing, including how relational values inform everyday fishing practices, cultural and place identities, as well as interactions with others and connections to the marine environment. Top-down approaches used in MPA development worked against key relational values, including social cohesion, reciprocity, place, agency and self-determination to dismantle and disrupt the practices SSFs viewed as fundamental to their livelihood and collective wellbeing. Our findings serve as a starting point to better recognize the context specific factors that underlie relational wellbeing and give insight into how relational values shape social-ecological complexity within coastal communities. The paper highlights how the international marine conservation community can better account for and foster relational wellbeing and relational values to achieve the goals of both human wellbeing and marine biodiversity conservation.